High-Glucose Enhances a Thromboxane A2-Induced Aortic Contraction Mediated by an Alteration of Phosphatidylinositol Turnover - Koji Nobe; Hikaru Suzuki; Hiromi Nobe; Yasushi Sakai; Kazutaka Momose (Elsevier, 2003)
The effect of the thromboxane A2 analogue U46619 (9,11-dideoxy-11α,9α-epoxymethanoprostaglandin F2α) on sustained contraction in the mouse aorta was investigated. U46619 induced concentration-dependent (1 - 100 nM) increases in contraction. These contractile responses were enhanced significantly under high-glucose-physiological salt solution (HG-PSS) (2-fold greater than normal-PSS) conditions. This hyperactivation may be associated with aortic dysfunction in diabetes. However, the mechanisms remain unclear. HG-PSS enhanced U46619-induced accumulation of endogenous diacylglycerol (DG). Phospholipase C inhibitor (U73122) suppressed DG accumulation under normal conditions; however, suppression was not observed under high-glucose conditions. The HG-PSS-induced enhancement of contraction was inhibited by protein kinase C (PKC) inhibitor (calphostin C). This result indicated that accumulated DG might increase PKC activity, which then stimulates DG kinase activation as a feedback mechanism. DG kinase inhibition also suppressed HG-PSS-induced enhancement of contraction. Increased myo-inositol incorporation was detected under high-glucose conditions, indicating an acceleration of phosphatidylinositol (PI)-turnover. Moreover, rho kinase inhibitor (Y27632) suppressed U46619-induced contraction exclusively in normal-PSS. These findings indicated that HG-PSS treatment increases DG synthesis derived from incorporated glucose, PKC and DG kinase activation, and enhances the U46619-induced contraction via acceleration of PI-turnover. This series of responses may be involved in the dysfunction of aorta under high-glucose conditions occurring in association with diabetes.